THE RESPONSIBILITY OF LEGAL OFFICERS IN OVERCOMING LEGAL PROBLEMS IN A ROTATING EQUIPMENT REPAIR AND MAINTENANCE SERVICE COMPANY - Rabbani, Tezar; Putri, Elfirda Ade; Hirwansyah (Program Studi Hukum, Universitas Muhammadiyah Sukabumi, 2025)
A Limited Liability Company is a legal entity that is not responsible for the personal property of shareholders, except as regulated in Law No. 40 of 2007 and Law No. 6 of 2023 concerning Job Creation. This study aims to analyze the responsibilities and positions of Legal Officers at PT Japa Indotama and PT Langgang Buana Perkasa using normative juridical methods. The normative approach is carried out by discussing regulatory aspects and case studies. Data were obtained through interviews and included primary, secondary, and tertiary legal materials, which were analyzed descriptively analytically. The results show that Legal Officers have an important role and require a background in legal education, but there is no special arrangement other than referring to Article 103 of Law No. 40 of 2007. It is recommended to establish special regulations to clarify the position, professionalism, and competency standards of Legal Officers.